1992
DOI: 10.1007/bf00271288
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical demonstration of glutamate dehydrogenase and phosphate-activated glutaminase activities in semithin sections of the rat retina

Abstract: The activities of the glutamate metabolizing enzymes phosphate-activated glutaminase (PAG) and glutamate dehydrogenase (Gldh) are demonstrated in semithin sections of the rat retina. Highest activities of both enzymes are found in the photoreceptor inner segments, PAG additionally in the outer plexiform layer and Gldh in the inner plexiform layer and in mueller glial cells. Although their non randomly distribution makes a role in neurotransmitter metabolism possible, their high activities in inner segments poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Previous studies have shown that PAG activity in the rat retina is highest in the photoreceptor inner segments, and of similar activity across the inner nuclear, inner plexiform, and ganglion cell layers (Ross et al, 1987;Gebhard, 1992). In this study, glutamine immunoreactivity was localized in photoreceptor inner segments, bipolar cells, horizontal cells, Muller's cells, and some…”
Section: Results Immunocytochemistrymentioning
confidence: 53%
“…Previous studies have shown that PAG activity in the rat retina is highest in the photoreceptor inner segments, and of similar activity across the inner nuclear, inner plexiform, and ganglion cell layers (Ross et al, 1987;Gebhard, 1992). In this study, glutamine immunoreactivity was localized in photoreceptor inner segments, bipolar cells, horizontal cells, Muller's cells, and some…”
Section: Results Immunocytochemistrymentioning
confidence: 53%
“…Müller cells possess enzymes that are involved in the de novo synthesis of glutamate from pyruvate, e.g., pyruvate carboxylase, that catalyzes the carboxylation of pyruvate to oxaloacetate as substrate of the Krebs cycle, and glutamate dehydrogenase, that converts α-ketoglutarate to glutamate (Gebhard, 1992; Ola et al, 2011a). Glutamate dehydrogenase is able to metabolize glutamate at relatively low pH (Zaganas et al, 2012) that prevails in glial cells following glutamate uptake (Bouvier et al, 1992).…”
Section: Glutamate Uptake and Metabolismmentioning
confidence: 99%
“…Secondly, this trend might be attributable to disruption of energy metabolism including glutamate due to ischemia. Except for glutamine synthetase, enzymes for glutamate metabolism including glutamate dehydrogenase (GDH), phosphateactivated glutaminase, aspartate aminotransferase and ornithine aminotransferase show the highest level of activity in the photoreceptor inner segments [26][27][28] . Ischemia increases intracellular ammonia concentration in rat retinas [25] .…”
Section: Discussionmentioning
confidence: 99%